2017
DOI: 10.7150/ijbs.17149
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lipin-1 induces insulin resistance by increasing intracellular ceramide accumulation in C2C12 myotubes

Abstract: Dysregulation of lipid metabolism in skeletal muscle is involved in the development of insulin resistance. Mutations in lipin-1, a key lipid metabolism regulator leads to significant systemic insulin resistance in fld mice. However, the function of lipin-1 on lipid metabolism and insulin sensitivity in skeletal muscle is still unclear. Herein we demonstrated that downregulation of lipin-1 in C2C12 myotubes by siRNA transfection suppressed insulin action, characterized by reduced insulin stimulated Akt phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…A restoration of insulin-stimulated Akt phosphorylation, despite an increase in DAG concentrations, was observed [70]. The dominance of ceramide influence versus DAG in muscle cells was confirmed in a recent study showing that lipin-1 silencing impaired insulin sensitivity in C2C12 myotubes [82]. Interestingly, the authors observed decreased intracellular DAG levels and increased ceramide accumulation in these cells [82].…”
Section: Ceramide Vs Dag As Modulators Of Muscle Insulin Sensitivitymentioning
confidence: 80%
“…A restoration of insulin-stimulated Akt phosphorylation, despite an increase in DAG concentrations, was observed [70]. The dominance of ceramide influence versus DAG in muscle cells was confirmed in a recent study showing that lipin-1 silencing impaired insulin sensitivity in C2C12 myotubes [82]. Interestingly, the authors observed decreased intracellular DAG levels and increased ceramide accumulation in these cells [82].…”
Section: Ceramide Vs Dag As Modulators Of Muscle Insulin Sensitivitymentioning
confidence: 80%
“…They found that insulin sensitivity in such individuals is inversely correlated to the ceramide species C18:0, C20:0, C24:1 and to the total plasma ceramide level. The accumulation of ceramides produced from palmitate (through the de novo pathway) has been found to induce an inhibition of insulin signalling ( in vitro ) and diabetes ( in vivo ) . Chavez and Summers in 2012 also emphasized the role of ceramides in insulin resistance and presented a new hypothesis that implicated ceramides as a key agent in the development of insulin resistance.…”
Section: Ceramides and Insulin Resistancementioning
confidence: 99%
“…The lower expression of PEMT we found in VAT and the lower accumulation of lipid droplets in PEMT-deficient adipocytes are also in agreement with the findings of several groups that reported a (somewhat counterintuitive) lower adipocyte size in VAT ( 32 , 33 ) and its association with insulin resistance ( 34 ). Further studies demonstrate that PEMT expression is regulated by insulin ( 35 , 36 ), and that ceramides induce insulin resistance ( 37–39 ). Taken together with these studies, our network-based analysis and our stem cell model suggest that PEMT forms a major metabolic junction that bridges a few biosynthetic pathways into a functional pathway in adipose tissues.…”
Section: Discussionmentioning
confidence: 99%